Teleios Dalam Perjanjian Baru: Analisis Teologis dan Relevansi bagi Kehidupan Kristen - Febri, Hendrikson (PASCA : Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
This study explores the theological meaning and implications of the term teleios in the New Testament, as well as its relevance to the lives of believers. The term teleios carries profound significance as a guide toward achieving a life purpose aligned with God's original design. The objective of this research is to theologically and contextually analyze the meaning of teleios in the New Testament and its implications for Christian living. The findings reveal that the concept of teleios emphasizes that the Christian life of faith is a dynamic process of growth. Believers are called to mature in spiritual maturity and completeness, enabling them to fulfill divine purposes, live in unity with Christ, and become effective witnesses to the world. Achieving the fullness of life as designed by God requires commitment, perseverance, and complete dependence on God.